The Weak Soil Investigation at the Slope Zone in the Hot Spring Area, Rokan Hulu, Indonesia - Nur Islami (UIR PRESS, 2019)
The slope failure can occur due to the soil on the slope area is relatively porous and the surface water is easily to move in the soil. The zone of the weak zone of the soil should be detected early to avoid the ground mass movement on the slope area. This study is to investigate the weak zone of the soil on the slope area of the hot spring tourism location using geoelectrical resistivity and soil property analysis methods. The Wenner configuration with a total of 40 electrodes has been employed at each four resistivity survey lines. The electrode spacing was adjusted to be 2 – 5 meter in order to get relatively higher resolution of the resistivity data. Soil samples were collected at several site to measure the soil characteristics of the study area. The soil analysis results show that the study area consist of gravel, sand, clay, silt and weathered methasediment. The geoelectrical resistivity model shows the relatively low resistivity value of about 30 ohm.m at the slope zone which is indicating that the soil has higher porosity. Generally only a few locations with the weak soil zone detected in the slope of the hot spring area, however, it is not potential for the ground mass movement due to the soil is relatively thin.